A rapid and sensitive assay for histone acetyl-transferase activity (1998)
Histone acetyl-transferases (HATs) seem to be key elements in the regulation of transcription. We have designed an enzymatic assay to quantify HAT enzymatic activity. In this assay, the substrate is a peptide corresponding to the 24 first amino acids of histone H4 which is coupled to biotin. After acetylation using [14C]acetyl-CoA, the peptide is purified on streptavidin beads and the associated radioactivity is measured. This assay is sensitive, rapid and convenient.